PEMBERIAN SANKSI KEPADA HAKIM SEBAGAI PENEGAK HUKUM YANG MELANGGAR KODE ETIK - Tsabitha, Tanissa Mayra; Lesmana, Idham Putra; Ramdhani, Dwi Sukma; Hidayat, Erika Maharani; Hezron, Alessandro Christoper Max; Saly, Jeane neltje (Peneliti.net, 2023)
This article now the content of the ethics rules for judges, which apply to sanction violations of every Code of Ethics. The technique selected by the author is a normative injunction research method that polestar on the study of legal norms. One of the infraction of the Code of Professional Decency affairs the profession of judges, whichever is reflected in the oversight of judges, which is catalogued in Article 1, Item 6, of Law No. 18 of 2011 on Respect and Obedience to Judicial Conduct. A code of ethics is a set of rules and principles that govern the conduct and burden of professionals in the legal field. The Code of Ethics is calculated to ensure that they carry out their work alongside a high degree of responsibility, integrity, honor and probity. However, unprofessional conduct persists, with in the court.